Pengaruh Kombinasi Konsentrasi Pupuk Daun Bayfolan dan Ekstrak Kecambah Kacang Hijau/ Tauge (Vigna radiata L.) Terhadap Pertumbuhan Tanaman Buncis Tegak (Phaseolus vulgaris [L.] cv. Balitsa 2) - Tia Setiawati; Maulidiyah Maulidiyah; Mohamad Nurzaman; Asep Zainal Mutaqin (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2018)
The growth of bean plants can be enhached through the provision of fertilizer and organic material. The purpose of this research is to get the best concentration of Bayfolan leaf fertilizer and mung bean sprout (Vigna radiata L.)extract in improving the growth of green bean plants(Phaseolus vulgaris [L.] cv. Balitsa 2). This study was conducted using an experimental method in the greenhouse with a single factor Block Randomized design (BRD) consisting of 20 combinations of Bayfolan fertilizer and the extract of mung bean sprouts (V. radiata). Bayfolan fertilizer concentration used was 0, 2, 2.5, and 3 mL / L, while the concentration of bean sprout extract used was 0%, 20%, 40%, 60%, and 80%. The results of the Analysis of Variance (ANOVA) showed that the combination of 3 mL/L Bayfolan foliar fertilizer and 60% extract of mung bean sprouts was the best concentrations for the growth of green bean plants on plant height parameters, the number of leaves, the number of flowers, wide of leaf, and the weight of dried bush bean plants. Keywords: Phaseolus vulgaris, extract of mung bean sprouts, Bayfolan fertilizer, growth.